Biological Antivirals for Treatment of Adenovirus Infections. Issue 7 (October 2016) - Schaar, Katrin; Röger, Carsten; Pozzuto, Tanja; Kurreck, Jens; Pinkert, Sandra; Fechner, Henry
Adenovirus (Ad) infections are usually mild and self-limiting, but severe systemic infections and fatal diseases can occur, especially in immunosuppressed patients. Anti-adenoviral pharmacotherapy has been proven to inhibit Ad infection, but its efficiency is limited. This review addresses biological antiviral agents as a new class of therapeutics for treatment of Ad infections. One group of agents is composed of short double-stranded RNA molecules that have been developed to inhibit Ad receptor and Ad protein expression. The second group of agents includes soluble virus receptor traps which inhibit Ad uptake into cells. Anti-Ad-adoptive T-cell therapy constitutes a third approach. We also outline how the combination of biological antiviral agents and combinations of these agents with the classical antiviral drugs can increase therapeutic efficiency in anti-adenoviral treatments.